2001
DOI: 10.1046/j.0953-816x.2001.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of leptin receptor proteins in afferent and efferent neurons of the vagus nerve

Abstract: Leptin, the product of the ob gene, plays a key role in the regulation of food intake via a cross-talk between hypothalamic leptin receptors and neuropeptides that affect feeding behaviour. Recent studies have shown a synergistic interaction between leptin and cholecystokinin (CCK) leading to suppression of food intake, which involves CCK-1 receptors and capsaicin-sensitive vagal fibres. In this study, we have investigated the presence of leptin receptors in afferent and efferent neurons of the vagus nerve. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 51 publications
5
105
0
3
Order By: Relevance
“…Leptin is produced in the mucosa of the stomach and rapidly mobilized by feeding and high doses of exogenous cholecystokinin (Bado et al, 1998), and it appears to activate vagal afferents (Wang et al, 1997), shown to express the long form of leptin receptor (Buyse et al, 2001;Burdyga et al, 2002). Small doses of leptin infused into the celiac artery significantly decreased sucrose intake and this effect was not observed in rats with subdiaphragmatic vagotomy or perivagal capsaicin-treatment aimed to selectively ablate vagal afferent fibers.…”
Section: Stomach: Stretch Tension Leptin and Ghrelinmentioning
confidence: 99%
“…Leptin is produced in the mucosa of the stomach and rapidly mobilized by feeding and high doses of exogenous cholecystokinin (Bado et al, 1998), and it appears to activate vagal afferents (Wang et al, 1997), shown to express the long form of leptin receptor (Buyse et al, 2001;Burdyga et al, 2002). Small doses of leptin infused into the celiac artery significantly decreased sucrose intake and this effect was not observed in rats with subdiaphragmatic vagotomy or perivagal capsaicin-treatment aimed to selectively ablate vagal afferent fibers.…”
Section: Stomach: Stretch Tension Leptin and Ghrelinmentioning
confidence: 99%
“…In these studies, peripherally administered leptin prevented food-deprivation-induced decreases in circulating leptin (figure 2a,b; Keen-Rhinehart & Bartness 2008) and attenuated food-deprivationinduced increases in food hoarding, being most effective in hamsters with the lowest foraging effort requirement (figure 1c-e; Keen-Rhinehart & Bartness 2008). It is generally accepted that leptin penetrates into the brain to act centrally to affect ingestive behaviour (Elmquist 2001), although evidence of leptin receptors on vagal sensory nerves (Buyse et al 2001) suggests an additional means by which peripheral leptin could affect food intake (but ultimately acting centrally as well). Indeed, in our studies, leptin more effectively blocked food-deprivation-induced increases in food hoarding when given centrally, inhibiting fooddeprivation-induced increases in food hoarding up to 48 h post-injection regardless of foraging requirement (figure 3a -c; Keen-Rhinehart & Bartness 2008).…”
Section: Peripheral Physiological Factorsmentioning
confidence: 99%
“…ObRl is highly expressed in the hypothalamus (Bjorbaek et al, 1997). However, lower levels of ObRl have been identified in many peripheral organs (Morton et al, 1999;Frank et al, 2000;Buyse et al, 2001;Goiot et al, 2001;Akerman et al, 2002;Ebenbichler et al, 2002;Lee et al, 2002;Kim et al, 2003).…”
Section: Leptin Signalingmentioning
confidence: 99%